Integrated IoT Monitoring, Tracking, and Cleaning System for PV Floating Structures - Hairuddin, Hariz Saifuddin; Jabbar Al-Fattah Yahaya, (Evolution in Electrical and Electronic Engineering, 2023)
Floating solar photovoltaic (FSPV) systems, also known as floatovoltaics, have emerged as promising clean energy solutions with numerous environmental benefits. This paper presents a comprehensive study of FSPV systems, focusing on their advantages, implementation methods, and efficiency analysis. The project involved the development and testing of three key systems: a tracking sun position system, a cleaning robot PV panel system, and an Internet of Things (IoT) monitoring power system. The materials and methods employed in this project are also described, involving the use of various hardware components such as Arduino microcontrollers, sensors, motors, and software tools like Arduino IDE and Blynk. The results and discussion section presents the testing and calibration of voltage and current sensors, the functionality of the tracking sun position system, and the challenges faced in the implementation of the cleaning robot PV panel system. While the cleaning robot system encountered certain motor-related issues, the overall implementation of FSPV systems demonstrated the IoT monitoring power system can help users or engineers monitor floating PV panels successfully.